The construction of a quality index for open television - Mir, M. Angélica (2022)
This article presents the genesis/development of the construction of a quality index for open television in Chile, the main findings of its application in the year 2007 and their comparison with the findings obtained in 2006. A theoretical analysis of the concept of quality in the mass media industry, and a qualitative study that shed light on the concept from the viewpoint of the industry as well as that of TV audiences and advertisers, provided the background to generate an index whose main strenght is that it integrates the opinion of viewers, their behaviour, the intrinsic quality of the product and the distinction as much as in the form as in the contents according to programming genre. The results of the second application of this index show that in terms of quality, Chilean television is considered to be average middling, with news programmes as the best evaluated and miscellaneus/general entertainment programmes with the poorest evaluation.